PENDAMPINGAN DAN EVALUASI KETERSEDIAAN AIR IRIGASI WILAYAH KELOMPOK TANI RAHARJO DESA GUMUKMAS, KECAMATAN GUMUKMAS, KABUPATEN JEMBER - Pambudi, Akbar Setyo; Andriyani, Idah; Hita, Muhammad Arga; Karomah Hidayah, Darul Alfan; Abiyyu, Ahmad Naufal; Arif, Ahmad Zidan; Jones, Mochammad Roy (LP2M Universitas Jember, 2025)
Irrigation is an effort to provide water, manage water (management), and drainage for plant needs. Raharjo Farmers Group is one of the farmer groups in Gumukmas Village, Gumukmas District, Jember Regency, which is located close to the coastal area or can be said to be the most downstream area of ​​the flow. This research activity entitled